Real-Time Revenue Assurance Automation Technology: Factors Influencing Its Adoption by Retail Banks in Cameroon - Tatang Ghogomu, David (Digital Repository of Theses, 2023)
Loan interest revenue of retail banks in Cameroon and the world at large constitutes a material revenue source respectively amounting to billions in local currency (up to XAF 82 billion) and US dollars. It further has the particularity that it is a derived revenue which lends itself, in its detennination, to human intervention thus susceptible to fraud that stack up to substantial financial losses to retail banks in Cameroon. Additionally, recent technological advances such as computer, broadband networking, internet, mobile telephone, Enterprise Resource Planning, sensors and extensible business reporting language which when combined are capable of initiating and finalizing bank transactions almost instantaneously on a global reach thereby require faster management decision-making. Against this backdrop, this study purposefully and empirically investigated the factors influencing the adoption of real-time revenue assurance automation technology(RT-RAA T) by retail banks in Cameroon using the theory of reasoned action (TRA) and extended by culture. Designed as an applied, explanatory, deductive, quantitative and cross-sectional research, self-administered questionnaires were used to collect primary data from a sampling frame of sixteen retail banks in Cameroon using simple random sampling which resulted in 135 respondents after respecting stratification criteria. Microsoft Excel and GNU PSPP Statistical Analysis Software were used for data analysis. The results found that attitude and subjective nonn, two of the constructs of the theory of reasoned action, Hofstede's (1994) national culture and its uncertainty avoidance dimension and market culture type of organizational culture were the significant factors influencing intention to use RT-RAAT withfo retail banks in Cameroon. The TRA singularly explained 60% of the variation in intention to use RT-RAA T compared to TAM at 40% in other studies. When extended by culture, it explained 81 % of variations in ITU. The study respectively mapped national and organizational culture landscapes of Cameroon and its retail banks. It found Cameroon to be high on three of the four cultural dimensions of Hofstede's (1994) national culture index scale relative to world average and the dominant organizational culture of the retail banks to be hierarchy culture based on Cameron and Quinn's (I 999) OCAI framework. The study was pioneering in its recommendation for preliminary predictions of technology adoption using Ji near models, such as proposed in this study, to be incuded as one of the key activities of the feasibility study stage of technology adoption generally and RT-RAAT in particular.